1993
DOI: 10.1161/01.cir.88.4.1845
|View full text |Cite
|
Sign up to set email alerts
|

Role of ATP-sensitive K+ channel on ECG ST segment elevation during a bout of myocardial ischemia. A study on epicardial mapping in dogs.

Abstract: The findings of this study suggest that the activation of ATP-sensitive K+ channels during a bout of acute myocardial ischemia plays an important role in the emergence of ECG ST elevation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…15 Kubota et al demonstrated that intracoronary infusion of another potassium channel opener, pinacidil (10 g kg -1 min -1 ), induced ST-segment elevation on epicardial ECGs in anesthetized open-chest dogs. 16 They showed that pretreatment with intracoronary glibenclamide, which blocks the ATP-sensitive potassium channel, attenuated the ST-segment elevation in both dogs with acute myocardial ischemia and pinacidil-treated dogs. Electrocardiographic changes after intracoronary injection of nicorandil have not been previously investigated; however, we speculate that some different mechanisms may account for the nicorandilinduced higher ST-segment elevation.…”
Section: Potassium Channel Opener and St-segment Elevationmentioning
confidence: 99%
“…15 Kubota et al demonstrated that intracoronary infusion of another potassium channel opener, pinacidil (10 g kg -1 min -1 ), induced ST-segment elevation on epicardial ECGs in anesthetized open-chest dogs. 16 They showed that pretreatment with intracoronary glibenclamide, which blocks the ATP-sensitive potassium channel, attenuated the ST-segment elevation in both dogs with acute myocardial ischemia and pinacidil-treated dogs. Electrocardiographic changes after intracoronary injection of nicorandil have not been previously investigated; however, we speculate that some different mechanisms may account for the nicorandilinduced higher ST-segment elevation.…”
Section: Potassium Channel Opener and St-segment Elevationmentioning
confidence: 99%
“…Data were digitized at a sampling frequency of 1000 Hz in each electrogram (CD-G015; Chunichi Denshi) and was stored on magneto-optical disks for later analysis as described in the previous study. 1,12 Experimental Protocol Protocol 1: Induction of ST a by Disopyramide, Lidocaine, or Flecainide…”
Section: Mapping Of Epicardial Electrogramsmentioning
confidence: 99%
“…All recording electrodes were referenced to the Wilson's central terminal, and multichannel electrograms were digitized every millisecond using a multiplexed data processing system (CD-G015, Chunichi Denshi, Nagoya, Japan) as described in a previous study. 14 The thoracic cavity was covered with plastic wrap to prevent cooling and dehumidifying. Body temperature was maintained at 37-38°C.…”
Section: Instrumentationmentioning
confidence: 99%
“…14 The cross-correlation function was used to reject ectopic beats and artifacts (cross-correlation coefficients below a threshold value: 0.95). 16 The number of beats averaged was from 50 to 56 (mean, 54).…”
Section: Analysis Of Multichannel Epicardial Electrogramsmentioning
confidence: 99%